PENGARUH KOMPENSASI, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA KERTA RAHARJA KABUPATEN TANGERANG - Darmadi Darmadi; Ratna Sari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The regional drinking water company/ PDAM Tangerang district realizes the importance of performing employees. This is a necessity of the goals to be achieved. Therefore, this study was conducted to review what factors can affect the performance of PDAM Tangerang district employees. To test this phenomenon, a quantitative approach was used by distributing Likert-scale questionnaires. Based on Slovin's calculations, the number of samples obtained is 186 people. In distributing the questionnaire, a simple random technique was used. The results of the study suggest that the compensation variable is the most influential factor on the performance of PDAM Tangerang district employees, this confirms the importance of a good reward system, so that employee performance and productivity are maintained. In addition, the variables of culture and motivation partially and simultaneously have a significant effect on increasing performance. Implicitly, the existence of work values ??determined by the task execution method has a significant effect on improving performance. Likewise with the spirit of work, with a sense of pleasure and optimism, it gives birth to a good work pattern so that it has an impact on increasing the quantity and quality of work.